An Assessment of Response to Conversation Cues of Uninterest Conducted via Telehealth. Issue 2 (March 2023) - Kishel, Catherine; Vollmer, Timothy
Individuals diagnosed with autism spectrum disorder (ASD) exhibit deficits in social interaction and communication. Kronfli, Vollmer, et al. developed an in-person assessment to evaluate participant response to social cues indicating uninterest in a conversation. In the current study, we sought to extend these procedures to the assessment of conversation skills via telehealth given the ongoing pandemic and so that participants in remote areas could receive services. Participants were exposed to a hierarchy of social cues of uninterest ranging in salience from one-word responses to a clear verbal statement of uninterest until they demonstrated sensitivity to a social cue. One participant who did not demonstrate sensitivity to any cues received instruction using Behavioral Skills Training. Initial results support the utility of using a remote assessment model to screen for sensitivity to specific social cues in conversations and to provide services to participants via telehealth.